Rubidium Fluoride Absorber Treatment for Wide‐Gap (Ag, Cu)(In, Ga)Se2 Solar Cells. Issue 6 (24th February 2022) - Keller, Jan; Aboulfadl, Hisham; Stolt, Lars; Donzel-Gargand, Olivier; Edoff, Marika
Abstract : This contribution studies the potential of an RbF postdeposition treatment (RbF‐PDT) of wide‐gap (Ag, Cu)(In, Ga)Se2 (ACIGS) absorbers to improve the corresponding solar cell performance. While a higher open‐circuit voltage ( V OC ) and short‐circuit current density are achieved, a lower fill factor (FF) is observed for most of the devices subjected to an RbF‐PDT. However, the drop in FF can be avoided for some close‐stoichiometric samples, leading to maximum efficiencies beyond 16% (without antireflection coating) at a bandgap energy ( E g ) of 1.43 eV. For off‐stoichiometric ACIGS, a record V OC value of 926 mV at E g = 1.44 eV is reached. Lower V OC deficits likely require enhanced bulk quality of wide‐gap chalcopyrite absorbers. Extensive material analysis shows that the heavy alkali PDT of ACIGS with high Ag and Ga contents leads to similar absorber modifications as commonly observed for low‐gap Cu(In, Ga)Se2 (CIGS). Rubidium is continuously distributed at "internal" (grain boundaries) and "external" (buffer and back contact) absorber interfaces. The results indicate that Rb diffusion into the absorber bulk (including 1:1:2 and 1:3:5 compounds) is restricted. Furthermore, the formation of a very thin RbInSe2 surface layer is suggested. It remains open, which effects alter the device characteristics after RbF‐PDT. Abstract : The effect of an RbF post deposition treatment for wide‐gap (Ag, Cu)(In, Ga)Se2 solar cells is studied. Absorber modifications similar to low‐gap Cu(In, Ga)Se2 are found, leading to an open‐circuit voltage ( V OC ) boost and allowing for thinner CdS (higher short‐circuit current density). Efficiencies up to 16.3% (without antireflection coating) at E g = 1.43 eV and a record V OC of 926 mV ( E g = 1.44 eV) are reached.